Sociological Analysis of Social Values in Short Stories Published in 2015 - D, Zulfardi (Research Horizon, 2025)
Literary works, particularly short stories, often serve as cultural reflections that embody and transmit social values within society. In Indonesia, newspapers remain an important medium for disseminating literature to the public, offering both entertainment and moral insights. Recognizing this potential, this research seeks to explore the social values embedded in selected short stories published by Singgalang Newspaper in 2015. The primary objective is to identify and analyze the categories of social values portrayed in the seven best short stories published during that year. Employing a sociological approach and a qualitative descriptive method, the analysis is guided by Kluckhohn’s theoretical framework on cultural values. The findings indicate that six of the seven stories embody social values reflected in various aspects, including the pursuit of ethical and meaningful life, the importance of competence and productivity in work, the awareness of existence within space and time, the skillful use of nature’s resources, and the cultivation of harmonious relationships among people despite social differences. The study demonstrates that short stories in mass media not only entertain but also function as effective vehicles for reinforcing essential cultural and social values.